MOLECULAR DOCKING STUDIES, SYNTHESIS AND ANTI-BACTERIAL PROPERTIES OF NEW MANNICH BASES - ONKARA.P,; A.SUNIL KUMAR,; S.KANAKARAJU,; B.PRASANNA,; Y.PYDISETTY,; G.V.P.CHANDRAMOULI, (International Journal of Pharma and Bio Sciences, 2013)
A series of 3-substituted aminophenyl-4-hydroxycoumarins 4a-h were synthesized via Mannich reaction by using [BMIM]BF4 ionic liquid under microwave irradiation. Compounds were characterized by IR, 1H NMR and mass spectroscopy. All the compounds were tested for their antibacterial activity against B.subtilis, Bacillus.sp, E. coli and P.putida. Most of the compounds showed moderate to good antibacterial activity. Docking studies of the synthesized compounds was done with the help of VLife MDS 3.5 software using GA docking method to study their observed activity.